Proximity to injustice: Leadership, basic needs, and institutional change in contexts of socially lived inequity in higher education - Ramirez, Jessica (My University, 2026)
Student basic needs insecurity in higher education is most often understood through measures of food insecurity, housing instability, and financial hardship. While these indicators reveal the scope of student precarity, they offer less insight into how such experiences are socially lived within universities and how they shape belonging, leadership, advocacy, and institutional change. Although food insecurity serves as a central focus of this study, it is examined within the broader context of basic needs precarity and the structural inequities that influence students’ experiences, opportunities, relationships, and pathways to engagement within higher education. This qualitative, intergenerational case study examines how lived experiences with poverty, basic needs insecurity, racial marginalization, and institutional inequity influence who becomes involved in social change efforts, what sustains engagement over time, and how responsibility for equity-related work is distributed across institutional roles and generations within a predominantly White institution (PWI). Situated at Kansas State University, the study traces institutional change efforts across five decades through the experiences of historic and contemporary actors, including the leadership of Dr. Bernard Franklin, the first Black student body president at Kansas State University during the 1970s; the institutional advocacy surrounding the creation of Cats’ Cupboard, K-State’s on-campus food pantry; and the experiences of students navigating food insecurity, race, and belonging in the present day. By examining these interconnected histories, the study explores how struggles for representation, inclusion, and student well-being become linked to broader efforts to address inequities within higher education. Positioned within these trajectories is my own autoethnographic journey from a food insecure undergraduate student and campus organizer to instructor, mentor, and researcher. Autoethnography serves not as personal backdrop but as a methodological through-line for examining how proximity to inequity evolves across time, role, and institutional position. Through this lens, lived experience is conceptualized not only as a structural condition but also as a source of knowledge and expertise through which individuals interpret inequity, navigate institutions, and mobilize others toward change. At the same time, the study examines how those most directly affected by systemic inequities often assume disproportionate responsibility for the labor of institutional navigation, care, advocacy, and reform. Grounded in Socially Lived Theory and informed by relational leadership theory, civic engagement scholarship, systems theory, and critical race theory, this study conceptualizes mobilization as relational, historically situated, and structurally embedded. Drawing on semi structured interviews, historical analysis, and reflexive qualitative inquiry, the study examines how leadership and advocacy emerge through the intersection of lived experience, institutional context, relational networks, and historical moment. This dissertation contributes to scholarship on leadership, civic engagement, student basic needs, food insecurity, and higher education by reconceptualizing motivation as socially lived, relational, and rooted in experiences of inequity. It extends existing research by examining lived experience not simply as a source of hardship, but as a catalyst for knowledge production, belonging, leadership, and institutional engagement. Practically, the study offers insight into how universities might cultivate more equitable and sustainable approaches to addressing student basic needs while recognizing the interconnected roles of representation, belonging, lived expertise, and institutional responsibility in shaping student success and well-being. Ultimately, the study argues that understanding who mobilizes for change, who sustains that work, and who bears its burdens requires attending to the socially lived realities through which inequity is experienced and contested across generations within higher education.
Keywords: Basic Needs; Leadership; Higher Education; Institutional Change; Socially Lived Theorizing; Civic Engagement